Impact of mass drug administration of azithromycin for trachoma elimination on prevalence and azithromycin resistance of genital Mycoplasma genitalium infection. (13th April 2019) - Harrison, Mark Andrew; Harding-Esch, Emma Michele; Marks, Michael; Pond, Marcus James; Butcher, Robert; Solomon, Anthony W; Zhou, Liqing; Tan, NgeeKeong; Nori, Achyuta V; Kako, Henry; Sokana, Oliver; Mabey, David C W; et al.
Abstract : Background: Mass drug administration (MDA) of 20 mg/kg (maximum 1 g in adults) azithromycin for ocular Chlamydia trachomatis (CT) infection is a key component of the WHO trachoma elimination strategy. However, this dose may be suboptimal in Mycoplasma genitalium infection and may encourage emergence of antimicrobial resistance (AMR) to azithromycin. Objectives: To determine the effect of MDA for trachoma elimination on M. genitalium prevalence, strain type and azithromycin resistance. Methods: A secondary analysis of CT-negative vulvovaginal swabs from three outpatient antenatal clinics (Honiara, Solomon Islands) from patients recruited either pre-MDA, or 10 months post-MDA in two cross-sectional surveys was carried out. Swabs were tested for M. genitalium infection using Fast Track Diagnostics Urethritis Plus nucleic acid amplification assay. M. genitalium -positive samples were subsequently tested for azithromycin resistance by sequencing domain V of the 23S rRNA DNA region of M. genitalium and underwent phylogenetic analysis by dual locus sequence typing. Results: M. genitalium prevalence was 11.9% (28/236) in women pre-MDA and 10.9% (28/256) 10 months post-MDA (p=0.7467). Self-reported receipt of azithromycin as part of MDA was 49.2% in women recruited post-MDA and 17.9% (5/28) in those who tested M. genitalium positive. Of samples sequenced (21/28 pre-MDA, 22/28 post-MDA), all showed a macrolide susceptible genotype. Strain typing showed that sequence types diverged into two lineages, with a suggestion of strain replacement post-MDA. Conclusion: A single round of azithromycin MDA in an island population with high baseline M. genitalium prevalence did not appear to impact on either prevalence or azithromycin resistance, in contrast to reported decreased genital CT prevalence in the same population. This may be due to limitations such as sample size, including CT-negative samples only, and low MDA coverage. Further investigation of the impact of multiple rounds of MDA on M. genitalium azithromycin AMR in antibiotic experienced and naïve populations is warranted.